PERANAN PUSAT PELAPORAN ANALISIS TRANSAKSI KEUANGAN (PPATK) DALAM MENCEGAH TINDAK PIDANA PENCUCIAN UANG DENGAN MODUS PRIVATE BANKING BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 2010 TENTANG PENCEGAHAN DAN PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG - Sandi Rambe, Rido Tri; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Developments in technology and the globalization of the banking sector, This makes the current banking has become the main target for money laundering activities because this is the sector which offers many services and financial instruments in traffic which can be used to hide the origin of a fund one of them with private banking mode. Indonesia itself has made efforts with the implementation of the law on Prevention and Combating Money LaunderingHowever, various modes arising causes are still many cases of money laundering one mode of private banking, this is the challenge that INTRAC (PPATK) able to increase its role in the prevention and combating of money laundering in private banking mode. with the necessary efforts to overcome the obstacles preventing and combating money laundering in private banking mode should be further enhanced by conducting periodic breakthroughs and improvements.The role carried out by INTRAC (PPATK) as FIU in the prevention and eradication of pencuican money with private banking mode is to receive reports, perform analysis, and forwards the results of the analysis to law enforcement officers.Keywords : Role - PPATK - Prevention of Money - Laundering